Students' Errors Analysis in Solving Problems in the Material of Sequences and Series based on Hadar's Criteria in terms of Students' Mathematical Understanding - Ilham Minggi; Bernard; Aco Fauzan (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This study aims to describe students' errors in solving problems in the material of Sequences and Series based on Hadar's criteria in terms of students' mathematical understanding. The type of research used is qualitative research with a descriptive approach. There are 6 research subjects, namely 2 students with high mathematical understanding, 2 students with moderate mathematical understanding, and 2 students with low mathematical understanding. The instrument used in data collection was an understanding test containing 7 questions, a series and series problem test containing 3 questions, as well as interview guidelines. The results showed that all subjects who worked on questions related to determining the P-th term in the series geometry and in working on problems related to determining the cattle population tend to make technical errors. Meanwhile, in working on problems related to determining the number of terms in an arithmetic sequence, the subject did not experience any errors in completing the answer except for the fifth subject and the sixth subject who did not answer at all.